Protective role of Kelulut honey against toxicity effects of polystyrene microplastics on morphology, hormones, and sex steroid receptor expresion in the uterus of rats - Amran, Nur Hanisah; Mohamad Zaid, Siti Sarah; Goh, Yong Meng; Salleh, Annas; Mokhtar, Mohd Helmy (Multidisciplinary Digital Publishing Institute, 2023)
Background: Microplastics (MPs) are an emerging global pollutant. Previous studies have revealed that chronic exposure to MPs can affect animal and human reproductive health, particularly by impairing the reproductive system’s normal functions, which may increase the risk of infertility in both males and females. Kelulut honey (KH), an excellent source of antioxidants, has been used to counteract the disruptive effects of Polystyrene microplastics (PS-MPs) in the rat uterus. Thus, this study aimed to investigate the potential protective effects of Kelulut honey against PS-MPs-induced uterine toxicity in pubertal rats. Methods: Prepubertal female Sprague Dawley rats were divided into four groups (n = 8): (i) normal control group (NC: treated with deionized water), MPs-exposed group (M: exposed to PS-MPs at 2.5 mg/kg), (iii) Kelulut honey group (DM: pretreated with 1200 mg/kg of KH 30 minutes before they were administered with PS-MPs at 2.5 mg/kg), and (iv) Kelulut honey control group (DC: only treated with KH at 2.5 mg/kg). The rats were treated orally once daily for six consecutive weeks. Results: Uterine abnormalities in PS-MPs-exposed rats were significantly improved after concurrent treatment with Kelulut honey. Morphology improvement was observed and luminal epithelial cells seemed thicker with more goblet cells, glandular cells had a more regular and circular shape, stromal cell increased in size, interstitial gaps between stromal cells expanded, and the myometrium layer was thicker. Kelulut honey treatment also effectively normalized the suppressive effect of PS-MPs on the expression and distribution of sex steroid receptors (ERα and ERβ), as well as the level of serum gonadotropin (LH and FSH) and sex steroid (estradiol and progesterone) hormones. Conclusion: Kelulut honey can protect the female reproductive system against the disruptive effects of PS-MPs. The phytochemical properties of Kelulut honey might be responsible for these beneficial benefits. However, future studies are warranted to identify the mechanisms involved.